Desnutrición en Enfermo Renal Crónico - Arley Vargas, Diego Armando (2019)
Protein-energy Wasting is a usual complication in the population with renal disorder, this is associated in an important way with the morbidity mortality of patients, mainly those who are on dialysis. The pathophysiological process is complex and acts as a vicious circle in this population. Timely diagnosis, prevention and treatment generate a positive impact on the nephropathic population, both in dialysis and in predialysis.